Knowledge and attitudes of physiotherapy students towards obesity - A. Awotidebe; J.S. Phillips (AOSIS, 2009)
Obesity has been recognised as a risk factor for non-communicable diseases, with more than one billion adults worldwide who are overweight, of which approximately 300 million are obese. Obesity puts an individual in danger of a shorter life expectancy and at risk for developing chronic diseases of life style, which includediabetes, cardio vascular disease and musculoskeletal disorders such as arthritis and back pain. Wide spread negative attitudes towards obese people have been observed which are equally prevalent among health care professionals.  This study was based on the need to determine the knowledge and attitudes towards obese people among physiotherapy students, as they are well suited to address theintricacies of obesity and its related conditions. One hundred and seventy five students from a university in the Western Cape, South Africa, completed a structured, self-administered questionnaire that was adopted from the Obesity Risk Knowledge and Fat Phobia Scale. The study sample demonstrated average levels of knowledge regarding obesity with scores ranging from 3 to 9 on a scale of 10 with a mean score of 6.05. A n overwhelming majority of the participants(> 80%) viewed obesity as largely a behavioural problem while nearly all the participants (97.6%) characterised obese people as lazy, unattractive, insecure and with lower self-esteem. This study has reinforced the need for a morefocussed approach to the education of physiotherapy students around obesity and obesity-related conditions, as well asthe management thereof.